Parâmetros de extrusão na produção de snacks de farinha de mandioca enriquecidos com caseína - Borges Lustosa, Beatriz Helena; Leonel, Magali [UNESP]; Mischan, Martha Maria [UNESP] (Universidade Estadual de Londrina (UEL), 2010)
This study aimed to evaluate the effects of operational conditions of the extrusion process (temperature, moisture and protein content) in production of cassava snacks added of casein, aiming to provide information to the cassava processing industry. The cassava flour and casein were characterized as their chemical components and color. The experimental design followed the central composite rotational design with three factors. The obtained products were characterized as for rate of expansion, specific volume, color and hardness. Data analyses showed that the lower moisture, protein and temperature conditions provided desired expanded products with light color attributes, high expansion and low hardness.
Extrusion parameters in snacks production from cassava flour and casein
Keywords: Cassava; extrusion; protein; expansion; color; texture